7 Use of GaN dosimeter in high dose rate Brachytherapy: A new approach of machines and patients quality controls. (December 2018) - Tournier, A.; Dabbagh, M.; Brun, T.
Abstract : Introduction: Brachytherapy uses sealed radioactive sources into the tumor. Due to the high dose per fraction and strong gradients in High Dose Rate Brachytherapy (HDR-BT), consequences on dose delivery may be significant if errors occur in the treatment workflow. In order to verify and ensure that the dose is correctly delivered, periodic quality controls (QC) are carried out on machines according to the recommendations of the ESTRO BOOKLET 8. Many tools, complex to use, exist. We therefore developed an quality assurance (QA) tool to check the mandatory machine parameters as well as the dose delivered. Methods: Dosilab has developed Securidose, an instrumented phantom using 4 Gallium Nitride (GaN) dosimeters. The phantom can host different inserts targeting afterloader QA and protocol QC up to 2 treatment channels. Specific calculation methods based on GaN dosimeter responses are used to accurately determine the dwell times and dwell positions (Fig. 1). We validated the Securidose system software and checked its accuracy with respect to the source dwell position and the measured dose according to the ESTRO guidelines (i.e. 2 mm and 5% respectively). This validation was achieved on 10 measurements with a prescribed dose of 5 Gy and repeated for the 3 inserts. Thereafter we introduced source positioning errors ranging from 1 to 10 mm to test the physical parameter error detectability as well as the impact on the dose. Finally, we developed a 6-channel insert (Fig. 1) to perform quantitative patient-specific QC measurements. Furthermore, measurements have been carried out on HDR-BT phantom to assess the Securidose system repeatability and reproducibility. Results: After ten successive measurement runs, we did not observe any significant deviations between the measured and planned source dwell positions and dose, as shown in Table 1. As shown on Fig. 2, we observed that the dose deviation exceeding the ESTRO recommendation of 5% are due to dwell deviation greater than 2 mm on the 1-channel insert and 3 mm for the 2 other insert types. Conclusion: Interests of this phantom are multiple; on the one hand afterloader quality controls can be done quickly and simply: source dwell position and delivered dose can be verified on the same acquisition run. On the other hand, the Securidose-equipped with the 6-channels insert allows quantitative verification of patient-specific treatment plans before treatment for both position and dose.